2021
DOI: 10.1177/20503121211040707
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and self-care practice on hypertension among antihypertensive medication users in a tertiary care hospital Nepal

Abstract: Background: Hypertension a “silent killer” is a serious global health problem, whose prevalence is increasing in Nepal. Objective: This study aimed to determine the attitude and practice of hypertension among anti-hypertensive medication users in a tertiary care teaching hospital in western Nepal. Methodology: A hospital-based cross-sectional study design was used among 136 hypertensive patients under medication, aged ⩾ 30 years, and visiting medical outpatient department, medical ward, and geriatric ward, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
3
7
0
2
Order By: Relevance
“…4, 58.3]. This study nding was consistent when compared with a study conducted in Harar, Ethiopia (49.6%) [29], (52.2%) Nepal [39], Dessie town, Ethiopia (49%) [31], and Debre Tabor, Ethiopia 54.1% [40]. This study nding was lower when compared with a study conducted in Nekemte specialized hospital, Ethiopia 68.92% [34], and Gondar, Ethiopia 59.4% [41].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…4, 58.3]. This study nding was consistent when compared with a study conducted in Harar, Ethiopia (49.6%) [29], (52.2%) Nepal [39], Dessie town, Ethiopia (49%) [31], and Debre Tabor, Ethiopia 54.1% [40]. This study nding was lower when compared with a study conducted in Nekemte specialized hospital, Ethiopia 68.92% [34], and Gondar, Ethiopia 59.4% [41].…”
Section: Discussionsupporting
confidence: 79%
“…Those hypertensive patients who had a favorable attitude towards Self-care were was 3.093 times [AOR = 3.093, 95%CI (1.198,7.990), p = 0.020] more likely to have good practice than those hypertensive patients who had an unfavorable attitude towards Self-care. This was supported by the study done in Harar, Ethiopia [29], and Nepal [39].…”
Section: Discussionsupporting
confidence: 57%
“…Thus, which is consistent with the current finding [ 30 ]. Moreover, a study from Nepal reported a comparable proportion (52.2%) of hypertensive patients having a consistent level of self-care practice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kesadaran pasien hipertensi akan penyakit hipertensi dan komplikasiya memegang peran penting pada kemauan, kemampuan, dan sikap positif pada pasien hipertensi untuk melakukan selfcare hipertensi dengan benar. Ditemukan hubungan yang kuat antara tingkat pengetahuan pasien hipertensi mengenai penyakitnya dengan tingkat kesadaran yang tinggi pada pasien hipertensi dan meningkatnya penerapan perilaku selfcare yang benar (Shrestha et al, 2021). Sementara jika kesadaran pasien hipertensi akan penyakitnya yang rendah, maka terjadi penurunan minat untuk melakukan tindakan selfcare hipertensi hipertensi yang menyebabkan pasien tidak mau melakukan tindakan selfcare hipertensi.…”
Section: Pembahasan Faktor Hambatan Berasal Dari Pasienunclassified